Factors associated with parental acceptance of the HPV vaccine in girls from metropolitan Lima, Peru - Valeria Juárez-Leon; Delahnie Calderón-Solano; Julio A. Poterico; Jorge Ybaseta-Medina; Diego Azañedo; J. Smith Torres-Román (BMC Public Health)
Abstract Background In 2022, cervical cancer was the second most common neoplasia among women in Peru, with 4809 cases and 2545 deaths reported. Infection with human papillomavirus (HPV) is a key factor in the development of this disease. Vaccination is the primary strategy for HPV prevention. Although HPV vaccination coverage has improved, evaluating acceptance profiles is crucial for effectively monitoring public immunization policies. We aimed to determine the associated factors with parental acceptance of the HPV vaccine in girls from Peru. Methods An observational, analytical, and cross-sectional study was conducted with a sample of 204 parents of girls and adolescents aged 9 to 19 years in Metropolitan Lima. The dependent variable was acceptance of the HPV vaccine, while the independent variables included demographic data, level of knowledge about HPV, and socioeconomic and cultural factors. Results A total of 204 parents participated in the study. Overall, 61.3% expressed willingness to vaccinate their daughters against HPV. Factors significantly associated with vaccine acceptance in the bivariate analysis included being a mother, being married, residing in the South-Central region, having a high monthly income, possessing private or public health insurance, and having a higher level of education. In both bivariate and multivariable analyses, having a daughter previously vaccinated against HPV was significantly associated with HPV vaccine acceptance, and remained the only independent predictor in the adjusted model (aPR = 1.25, 95% CI: 1.03–1.53, p = 0.023). Knowledge level about HPV was not significantly associated with vaccine acceptance in the adjusted model. Conclusion Prior experience with HPV vaccination was the strongest predictor of parental acceptance. Increasing awareness and addressing misconceptions through educational campaigns may enhance vaccine uptake.